Disparities in basic immunization coverage: a case study of supply and demand factors in two community health centers in Bogor, Indonesia - Hermadi; Nadjib, Mardiati (Universitas Gadjah Mada, 2025)
Purpose: To identify and analyze the factors influencing complete basic immunization (CBI) coverage at two community health centers (CHCs) with contrasting coverage levels. Methods: This study employed a qualitative approach with a case study design. Informants were purposively selected and included health workers, community health volunteers, and parents. We collected data through in-depth interviews and document review, then analyzed it using a qualitative thematic approach. Results: Supply-side factors included the number and competence of health workers, availability of facilities and infrastructure, and funding support. Demand-side factors comprised community knowledge and awareness, sociodemographic characteristics, and trust in vaccines. Ciapus faced shortages of health personnel and community resistance to immunization, while Bojong Nangka demonstrated active collaboration between health workers and the community. Conclusion: The disparity in CBI coverage between Bojong Nangka and Ciapus CHC is caused by an imbalance between supply and demand factors. In Ciapus, low coverage was driven by limited human resources, inadequate infrastructure, and insufficient funding (supply-side), as well as poor public knowledge, awareness, and trust in vaccines, and the minimal involvement of local leaders (demand-side). In contrast, Bojong Nangka succeeded by strengthening its supply and demand components. Comprehensive interventions are necessary to enhance immunization services, increase public awareness and participation, and thereby achieve equitable CBI coverage.